PROCESSING OF TITANIUM AND ALLOYS BASED ON IT - Botirov , Alisher Akhmadjon ugli (Educational Research in Universal Sciences, 2023)
Titanium and alloys based on it are among the materials of the new generation. Unlike other complex (construction) materials, titanium-containing materials have high physical and mechanical properties. It is characterized by high relative strength and heat tolerance, as well as resistance to corrosion and corrosion in an aggressive environment.